Treatment of psoriasis and psoriatic arthritis during pregnancy and breastfeeding - Kurizky, Patricia Shu (2015)
Psoriasis is a chronic inflammatory disease that affects primarily the skin and joints, with a worldwide incidence of 2-3%. Fifty percent of patients are women, most still diagnosed during childbearing years. Currently,the estimate is that up to 107 thousand deliveries are performed annually in women with psoriasis, a percentage of them in women with moderate to severe disease. Fetal risks in pregnant women with psoriasis derive both from maternal disease and the medications used to control the illness. The purpose of this review is to study the effect of the main drugs used in the treatment of psoriasis and psoriatic arthritis during pregnancy and lactation, with particular focus on disease-modifying anti-rheumatic biological drugs, biological therapies, immunobiologics or biologics.